Psychosocial factors play a central role in determining SNAP utilization for farm workforce - Rockler, Briana E.; Grutzmacher, Stephanie K.; Garcia, Jonathan; Smit, Ellen; Braverman, Marc (Frontiers in Public Health, 2024)
Federal food safety net programs, like the Supplemental Nutrition Assistance Program (SNAP), may not reach vulnerable populations like rural residents, immigrants, and Latinx individuals. Because these groups are overrepresented among the farm workforce, exploring SNAP utilization among farm communities may clarify the role it plays in alleviating food insecurity. In-depth interviews were conducted with 31 farmworkers and farm owners. Patterns and predictors of SNAP utilization were organized using an adapted Andersen Behavioral Model of Health Service Utilization. Psychosocial factors played the central role in participants’ use of SNAP. Opportunities to improve the design and delivery of SNAP include expanded eligibility cut-offs and targeted engagement mechanisms.